Interface-engineered Josephson junctions optimized for high JC. - Shimakage, H. (IEEE Transactions on applied superconductivity)
High-temperature superconducting interface-engineered junctions were fabricated using YBa2Cu3O7-δ on LaAlO3 (LAO) and sapphire substrates. We report on the improvements in the electrical characteristics by junction narrowing. Originally, the 2-μm-wide junctions had high critical current densities of 1.2 × 106 A/cm at 4.0 K and showed wide junction effects. Narrowing the junctions to below a micrometer reduced the wide junction effect over a large range of temperatures and the junctions had characteristic voltages of 5.16 mV at 4.0 K. The magnetic-field modulation of the critical current was also more ideal after narrowing. Furthermore, we show that interface engineered junctions on sapphire substrates have similar characteristics to those on LAO